The heavy-ion spin-orbit interaction - Brink, D; Sukumar, C (2002)
Vector polarization in a heavy-ion collision is influenced by coupling to inelastic channels. In the adiabatic approximation the coupling can be represented by an energy-independent induced spin-orbit interaction. The present paper presents a generalization which includes nonadiabatic effects as well as a contribution from the ground-state quadrupole moment. The derivation is based on second-order perturbation theory. The approximate effective spin-orbit potential includes the effects of the coupling to an inelastic channel for all values of the interaction time τ0. It reduces to the adiabatic approximation when τ0Δε/ℏ≫ 1 where Δε is the channel excitation energy. There is an application to the vector polarization observed in the scattering of 6Li and 7Li by 58Ni. © 2002 Elsevier Science B.V. All rights reserved.